Clinical response to chemoradiotherapy in esophageal carcinoma is associated with survival and benefit of consolidation chemotherapy. (6th July 2020) - Zhao, Zongxing; Zhang, Yanan; Wang, Xin; Geng, Xiaotao; Zhu, Liqiong; Li, Minghuan
Abstract: Purpose: Few studies have reported the impact of the clinical response of patients with Esophageal Carcinoma to chemoradiotherapy (CRT). Our study examines the association between clinical response and pretreatment variables, survival, patterns of failure, and benefit of consolidation chemotherapy in subjects with esophageal squamous cell carcinoma (ESCC) patients receiving CRT. Methods: Data from ESCC patients treated at Shandong Cancer Hospital between January 2013 and December 2016 were analyzed retrospectively. By definition, we considered a poor response as progressive disease (PD) and stable disease (SD), while complete response (CR) and partial response (PR) were considered as a good response. Multivariate analyses were carried out using Cox proportional hazards models and patient survival was assessed using the Kaplan‐Meier and log‐rank test. Results: After CRT, 136 (48.9%) patients responded well (good response) and 152 (51.1%) patients responded poorly (poor response). Overall survival (OS) and progression‐free survival (PFS) differed significantly between patients responded well and those responded poorly. Patients with an early‐stage or the upper location of the tumor were more likely to achieve a good response. Patients showing poor responses tended to experience local failure. The 3‐year OS and PFS rates of patients showing poor response were 38.9% and 25.5%, respectively, for the CRT with consolidation chemotherapy (CRT + C) group, and 22.7% and 16.7%, respectively, for the CRT group. However, patients with a good response did not benefit from the consolidation chemotherapy. Primary tumor location, T category, N category, and clinical response to chemoradiotherapy were independent factors predicting OS and PFS in ESCC. Conclusion: Clinical response to CRT substantially improves patient survival and is associated with failure patterns in ESCC. Consolidated chemotherapy may benefit patients with a poor response. Abstract : Our research analyzed the association of clinical response with pretreatment variables, survival, patterns of failure, and benefit of consolidation chemotherapy in esophageal squamous cell carcinoma (ESCC) patients treated with CRT. We found that clinical response to CRT is associated with significantly survival and failure patterns in ESCC patients. Consolidated chemotherapy may benefit patients with a poor response.